1993
DOI: 10.1159/000126551
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Δ<sup>9-</sup>Tetrahydrocannabinol on Tuberoinfundibular Dopamine Activity, Anterior Pituitary Sensitivity to Dopamine and Prolactin Release Vary as a Function of Estrous Cycle

Abstract: The effects of Δ9-tetrahydrocannabinol (THC) on the activity of brain dopaminergic neurons might be subject to gonadal influence. In this work, we tested this hypothesis in relation to the effects of THC on tuberoinfundibular dopaminergic (TIDA) activity, the anterior pituitary sensitivity to dopamine (DA) and prolactin (PRL) secretion. To this end, we examined the effects of an acute dose of this cannabinoid administered during different phases of the estrous cycle in the morning or afternoon. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…This limitation has to be considered in the interpretation of the data and further research will be addressed to evaluate the reasons for the sex-dimorphic alterations. However, it is important to note that in the female rat, sex steroids regulate both the expression and function of the endogenous cannabinoid system, so a potential explanation will also involve the impact of malnutrition on this important modulatory system, as it was described previously (Bonnin et al, 1993; Rodríguez de Fonseca et al, 1994). …”
Section: Discussionmentioning
confidence: 86%
“…This limitation has to be considered in the interpretation of the data and further research will be addressed to evaluate the reasons for the sex-dimorphic alterations. However, it is important to note that in the female rat, sex steroids regulate both the expression and function of the endogenous cannabinoid system, so a potential explanation will also involve the impact of malnutrition on this important modulatory system, as it was described previously (Bonnin et al, 1993; Rodríguez de Fonseca et al, 1994). …”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported that cannabinoid administration altered the activity of serotoninergic [18]and mainly dopaminergic [3, 7, 9, 18, 19, 20, 21, 22]neurons. These neurotransmitters are both involved, either directly or indirectly, in the control of neuroendocrine processes in the medial basal hypothalamus, in particular with regard to the control of PRL secretion.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have studied the effects of chronic treatment with either DA D| (SKF 38393) or Di (quinpirole) receptor ag onists on the acute neuroendocrine actions of a low dose (20 jag/kg) of HU-210. This low dose is very close to the ED50 observed for producing the classically described cannabinoid-induced neurobehavioral effects such as cat alepsy, immobility or analgesia [ 17,22,29], The study has been carried out using male Wistar rats, since we have recently described a possible modulation by sex steroids (estradiol and progesterone) of both hypothalamic canna binoid receptor density [30] and neuroendocrine effects of THC in both normal cycling and ovariectomized female rats [31]. We have analyzed: (a) plasma PRL, luteinizing hormone (LH), ACTH and corticosterone levels, (b) pitu itary PRL and LH contents and (c) the medial basal hypo thalamus (MBH) contents of DA, L-3,4-dihydroxyphenylacetic acid (DOPAC, the main DA intraneuronal me tabolite) and noradrenaline (NA).…”
Section: Introductionmentioning
confidence: 57%
“…On the day of analysis, the MBH were dissected as previously described [31] and assayed for monoaminergic parameters. This area consisted of a tissue block 2.5 mm deep extending from just caudal to the optic chiasm to the rostral margin of the mammillary bodies, and lateral to the hypothalamic sulci.…”
Section: Experimental Designmentioning
confidence: 99%